Morocco Moves Forward on an Arduous Path Reforming its Doing Business Indicators - Meneval, Philippe De; Hassan, Youssef Saadani; Abdulrazzaq, Ali Al (World Bank, Washington, DC, 2012)
The 2012 Doing Business (DB) Report lauds Morocco as the country that has achieved the biggest improvement in its ranking in 2011. The acknowledgment of the country's performance reflects a spectacular 21 place jump in its overall rank to 94, underpinning improvements and advances in four out of the 10 categories in the doing business index the success of the Comite National de l'Environnement des Affaires (CNEA) in implementing reforms over the last three years is likely to breed more success. The new government, formed in November 2011, declared renewed commitment to the CNEA, which is now recognized by various stakeholders as the legitimate focal point for business environment reforms. This achievement is expected to attract more support by the World Bank and other donors in the years ahead. There are still important challenges to the task of establishing a truly predictable and modern business environment in Morocco as indicated by its relative DB ranking, both globally and within the MENA region. Among these challenges is a need to further update and simplify laws on competition, concessions, the commercial code, collateral and bankruptcy and public procurement and to strengthen the capacity of various agencies for implementation. These reforms often take a long time as they extend over overlapping jurisdictions and agencies.